Forced convection condensation in novel cross-section tubes fabricated by selective laser melting - Lee, Yi Wei (Nanyang Technological University, 2020)
This report presents a numerical and experimental study of forced convection condensation heat transfer in tubes with different cross section designs in the stratified flow regime. A theoretical simulation was created to model the heat transfer coefficient of condensation and the simulation was developed using a programming code implemented in MATLAB®. The programme was also used to model forced convection condensation heat transfer in a circular tube, and the results of the simulation were analysed in detail to understand the mechanism causing the liquid film distribution. The simulation results for a circular tube were compared with existing published data, where most of the comparison show good agreement especially at high vapour quality. The reason for the disagreement at lower vapour quality might be due to the inaccurate vapour quality to void fraction correlation used in the simulation. Six different design models were proposed for stratified flow condensation. These models were created by joining circular arcs of different sizes at different orientations. The heat transfer performances of these models were compared to a circular tube of the same perimeter. The highest percentage increase in the heat transfer coefficient of 42.2 % as compared to a circular was reported for Model 6. Model 6 is a cross section formed by connecting 18 circular arcs of different radii. From this simulation, it is concluded that cross sections with strategically oriented and small radius circular arcs could reduce liquid film thickness and hence, increase the heat transfer performance. Model 2, a cross section formed by connecting four circular arcs of different radii was fabricated by the Selective Laser Melting technique, and was tested to determine its heat transfer coefficient using a condensation rig. The experimental heat transfer coefficients of Model 2 were compared to the simulation results. It was found that there is a large average deviation of 102.8 % between the experimental and simulation results. This deviation might be caused by the neglect of the tube surface roughness and the use of inappropriate correlations and approximation. Some recommendations for future work are proposed to obtain more accurate and reliable simulation results.